Zwierzęta w czasach nowożytnych (XVIII-XIX w.) Dane archeozoologiczne z badań na terenie osady w Nakonowie Starym stan. 2, gm. Choceń, woj. kujawsko-pomorskie - Osypińska, Marta (Folia Praehistorica Posnaniensia, 2014)
Archaeozoological research based on the 1159 animal remains analysis, recorded at the former locality of Nakonowo Stare village. The assemblage under studies was dated to the eighteenth-nineteenth centuries. Within typical post-consumption remains the cattle was the best represented (54%). Other species identified were pigs (19%), sheep/goats (9%), horse (11%), dog (4%), deer (0,08%), hen (0,8%) and goose (0,2%). The meat-oriented selection preferred animals unnecessary for the further breeding. The cattle kept in the eighteenth-nineteenth-century village was of the brahycerous type, 90-134 cm height, also pigs were rather small in size. The horses were more diverse, measuring 110-155 cm in the withers. Model of breeding and a meat consumption in Nakonowo Stare represented one of the three main scenarios for the domesticated stock usage in Central Europe.